1996
DOI: 10.1093/ajcp/105.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a Quantitative Immunoassay for Urine Myoglobin:Predictor in Detecting Renal Dysfunction

Abstract: A d a p t a t i o n o f a Q u a n t i t a t i v e I m m u n o a s s a y f o r U r i n e M y o g l o b i nThe authors describe the adaptation and optimization of the Stratus II serum myoglobin immunoassay to quantify urine myoglobin. In addition, the assay was used to accurately determine urine myoglobin concentrations in subjects at potential risk for myoglobin-induced renal dysfunction and the results obtained compared to conventional qualitative methods for urine myoglobin. The assay demonstrated with-in run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…These early methods took advantage of the pseudo-peroxidase activity of the heme moiety in myoglobin, but required complete removal of hemoglobin in the urine, which was difficult to achieve (3,9,10 ). The development of immunometric assays for myoglobin allowed more specific measurement and the potential for better predictive ability, such as in establishing a cutpoint for development of ARF (1,3,11 ). Despite this method development, the older, less-specific methods continue to be used.…”
Section: © 2009 American Association For Clinical Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…These early methods took advantage of the pseudo-peroxidase activity of the heme moiety in myoglobin, but required complete removal of hemoglobin in the urine, which was difficult to achieve (3,9,10 ). The development of immunometric assays for myoglobin allowed more specific measurement and the potential for better predictive ability, such as in establishing a cutpoint for development of ARF (1,3,11 ). Despite this method development, the older, less-specific methods continue to be used.…”
Section: © 2009 American Association For Clinical Chemistrymentioning
confidence: 99%
“…The study designs included 32 case series , 16 cohort studies (11,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and 4 case control studies (60 -63 ), for a total of 2399 subjects. Of the 52 studies, 16 measured uMb in only a portion of their study group.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium is the second most important intracellular cation after potassium and is found in all tissues. Magnesium stimulates bone growth and promotes the body's use of vitamins B, C, and E. It also plays a pivotal role in living beings and is vital in the biotope [3,4]. In human body, magnesium is present in various forms: as ionized, complexed, and protein bounded.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, initial CK levels were not found to be predictive of renal dysfunction in this study. Another report found that elevated urine myoglobin levels greater than 20,000 ng/mL were associated with a significantly increased risk of renal dysfunction [106].…”
Section: Assessing Risk Of Renal Failurementioning
confidence: 98%